Desalination of high-salinity water by membranes - GAO, AORAN (University of Waterloo, 2016)
This study deals with the desalination of high-salinity water using membranes by pervaporation. The membrane performance was characterized with water flux and salt rejection. It was shown that a water flux of 1.6 kg/m²h and almost complete salt rejection (99.9%) were achieved at 65℃. The water flux increased with an increase in temperature, and the temperature dependence of water flux obeyed an Arrhenius type of equation. The water flux decreased with an increase in the salinity of the feed solutions; increasing salt concentration from 1 to 20 wt% resulted in a 50% reduction in water flux, whereas the salt rejection was not influenced. The water flux varied with the type of the salts (i.e., NaCl, Na2SO4 and MgCl2) in the feed water, but the salt rejection remained over 99.9%, regardless of salt types and concentrations. Batch operation (10 hours) of desalination was studied to investigate the permeation flux variation in pervaporation process. The permeation flux continuously decreased during the course of operation, and when there was 20 wt% of salts in the feed solution, the water flux was 30% lower than pure water flux. The permeation flux could be recovered after the membrane surface was rinsed by water flow. In order to get an insight into water transport in the membrane, experiments were also carried out with membranes of different thicknesses. The water flux decreased with an increase in the membrane thickness from 39 to 88μm, and the membrane thickness dependence of water flux followed the Fick’s law. Mass transport in the membranes was analyzed quantitatively. The apparent diffusion coefficient of water was shown to decrease with an increase in salt concentration in the feed solution. The salt solubility in the membrane followed the order of MgCl2>NaCl>Na2SO4, and the salt permeability in the membrane followed the order of NaCl>MgCl2>Na2SO4. Moreover, the concentration profile within the membrane was also determined experimentally.
Keywords: desalination; pervaporation; high-salinity water; membrane